Sosyodemografik değişkenlerin hasta memnuniyetine etkisi - İçli, Gülnur Eti; Kuğuoğlu, Sema; Aslan, Fatma Eti (İktisadi ve İdari Bilimler Dergisi, 2006)
Patient satisfaction is an important measure of service quality (SQ) in health care organizations. Patient satisfaction and their expectations of care are valid indicators of service quality. This article reports the results of a survey patient satisfaction according to sociodemegraphic characteristics administered by interwiew in 1200 patients discharged from a university, goverment and social security hospital in Istanbul, Turkey. In this study, SERVQUAL scale was used for determining patient satisfaction with overall health care. Sociodemegraphic characteristics of the patients (gender, education level etc.) with regard to patient satisfaction were determined.